Farm mechanisation: balanced approaches - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The image of the broken-down tractor is one of the stereotypes of over-hasty development strategies. Sceptical reports about the failure of agricultural projects to meet ambitious targets are often accompanied by photos of rusting, inappropriate...